A polyphenol-rich prebiotic in combination with a novel probiotic formulation alleviates markers of obesity and diabetes in Drosophila. (September 2018) - Westfall, Susan; Lomis, Nikita; Prakash, Satya
Graphical abstract: Highlights: A synbiotic formulation alleviates multiple markers of diet-induced diabetes and obesity. The probiotic and synbiotic formulations have combinatorial metabolic action. dTOR and PPARy are potential regulatory targets of the synbiotic formulation. Synbiotics are potential therapeutic agents for diabetes and obesity. Abstract: Imbalances in the gut microbiota are directly associated with the pathogenesis of diabetes and obesity. The current study investigates how the combination of three probiotics Lactobacillus plantarum NCIMB 8826, L. fermentum NCIMB 5221 and Bifidobacteria longum subsp. infantis NCIMB 702255 with a novel polyphenol-rich prebiotic Triphala has combinatorial benefits on the symptoms and underlying mechanisms of diet-induced diabetes and obesity. Drosophila melanogaster fed either a high-fat (HFD) or high-sugar diet (HSD) were pretreated with individual or combined probiotic and/or prebiotic therapy. The individual probiotics elicited some beneficial effects on the physiological markers of diabetes and obesity including reductions in total weight, glucose and triglyceride levels with Lp8826 having a higher efficacy against HSD and Bi702255 against HFD stresses; however, a combinatorial effect was observed with the probiotic and synbiotic formulations. Further, the synbiotic formulation consistently rescued variations in insulin resistance and lipogenesis outlining the synbiotic's potential for treating metabolic disorders.